Forensic cultures in modern Europe (Manchester University Press, 2023)
This edited volume examines the performance of physicians, psychiatrists and other scientists as expert witnesses in modern European courts of law and police investigations. Its chapters discuss cases from criminal, civil and international law to parse the impact of forensic evidence and expertise in different European countries (Scotland, England, Germany, Spain, Italy, Russia, Portugal, Norway and the Netherlands) in the nineteenth and twentieth centuries. They show how modern forensic science and technology was inextricably entangled with political ideology, gender norms, changes in the law and legal systems. New scientific ideas and technology, such as blood tests and DNA, helped develop forensic science, but did not necessarily lead to a straightforward acceptance of expertise in the courtroom. Discussing fascinating case studies, the chapters in this book highlight how the ideology of authoritarian and liberal regimes affected the practical enactment of forensic expertise. They also emphasise the influence of images of masculinity and femininity on the performance of experts and their assessment of evidence, victims and perpetrators, for example in cases of rape, infanticide and crimes of passion. This book is an important contribution to our knowledge of modern European forensic practices, which, as several chapters underline, sometimes surprisingly diverge from institutional regulations.